An integrated transcriptomic analysis unveils the regulatory roles of RNA binding proteins during human spermatogenesis - Xu, Ning; Qin, Yixian; Liu, Yu; Guan, Yudong; Xin, Hang; Ou, Junwen; Wang, Yiqiao (Frontiers in Endocrinology, 2025)
BackgroundRNA-binding proteins (RBPs) have emerged as key regulators in testis development and spermatogenesis, yet a comprehensive understanding of their expression dynamics has been lacking.MethodsThis study leverages published single-cell RNA sequencing (scRNA-seq) data to elucidate the complex expression patterns of RBP genes during postnatal testis development and spermatogenesis. Additionally, it uses bulk RNA-seq data to explore the regulatory impact of RBPs on alternative splicing (AS) in non-obstructive azoospermia (NOA).ResultsWe have identified cell-specific RNA-binding protein (RBP) genes in various cell types throughout testis development. Notably, distinct RBP gene clusters exhibit significant differential expression, particularly in Sertoli cells as they mature from neonatal to adult stages. Our analysis has revealed temporally-regulated RBP clusters that correlate with the developmental progression of Sertoli cells and the advancement of spermatogenesis. Moreover, we have established links between specific RBPs and the pathogenesis of non-obstructive azoospermia (NOA) through the regulation of alternative splicing (AS) events. Additionally, RPL10, RPL39, and SETX have been identified as potential diagnostic biomarkers for NOA.ConclusionThis research provided an in-depth look at RBP expression patterns during human testis development and spermatogenesis. It not only deepens our basic comprehension of male fertility and infertility but also indicates promising directions for the creation of innovative diagnostic and treatment methods for NOA.